The Implementation Process of Comparable Worth: Winners and Losers - Orazem, Peter F.; Mattila, J. Peter (Journal of Political Economy, 1990)
This paper provides a unique opportunity to observe how a public policy affected the earnings of various interest groups at different stages of implementation. Specifically, we examine how the earnings of women, union members, and supervisory and professional staff were affected by various proposed and implemented comparable worth pay plans in Iowa. We find that large relative gains to women in the original proposed plans were reduced as the process evolved. As a result, some of the original gains to women were redistributed to union members, supervisors, and professionals.